Pengaruh Market Value, Leverage dan Assets Management Terhadap Firm Value dengan Kebijakan Dividen Sebagai Variabel Moderasi - Fanny Fanny; Indra Widjaja (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
An established company has two goals, short term and long term goals. In the long term goals, the company will try to maximize the value of the company. Maximizing firm value is essential for company because it means increasing the wealth of shareholders as well. This study examines the effect of market values, leverages, and management asset into the firm’s  value with dividend policy as a moderating variable. For this purpose, the firms in the sub-sector chemical listed in Indonesia Stock Exchange during the period of 2009 - 2018 are examined. The sampling method was done by using purposive sampling. Secondary data collection methods were taken from IDX published financial statements. This research used multiple regression analysis with fixed effect method to test their hypothesis using Eviews 9.0. The results show that earning per share has a negative significant effect to firm value in which is measured by price to book the value, while leverage and management assets have a positive significant impact to the firm’ value. F-test result shows that all independent variables in this research simultaneously has a significant effect to firm’s value with dividend policy as a moderating variable in sub sector chemical estate listed in Indonesia Stock Exchange. In the test of Adjusted R2, the analysis results showed that 43.41% firm’s value was influenced by the independent variables of this research while the remaining is influenced by other factors which are not studied.